A causal inference study exploring the impact of iron status on the risk of thyroid cancer based on two-sample mendelian randomization - Yihan Shi; Wenlian Zheng; Guanglun Yang; Hong Liu; Lei Xing (Discover Oncology)
Abstract Background & aims Thyroid cancer is prone to early lymph node metastasis.This study investigated the influence of iron status on thyroid cancer risk and its mediating role in the relationship between thyroid cancer incidence and thyroid cancer-related exposure factors. Method Utilizing iron status-related Single Nucleotide Polymorphisms as instrumental variables, the research analyzed summary data on iron status and thyroid cancer from Genome-Wide Association Studies following the Two-sample Mendelian randomization guidelines, primarily using the Inverse-variance weighted method, with Mendelian randomization-Egger method, weighted median method, simple mode, and weighted mode as supplementary analyses. The reliability and robustness of the results were assessed using the Leave-one-out analysis and Cochran’s Q Test. Results The findings indicate that the iron status has a vital causal relationship with the occurrence of thyroid cancer. The Inverse-variance weighted model results revealed Iron || id:ieu-a-1049: OR = 1.409, 95%CI = (1.043, 1.904), P < 0.05; Ferritin || id:ieu-a-1050: OR = 2.029, 95% CI = (1.081, 3.808), P < 0.05; Transferrin Saturation || id:ieu-a-1051: OR = 1.337, 95%CI = (1.058, 1.690), P < 0.05. The reliability and robustness of these results were further supported by the Leave-one-out analysis and Cochran’s Q Test (P > 0.05). Conclusion The study establishes a certain causal link between iron status and thyroid cancer, indicating that transferrin saturation, serum ferritin and serum iron are associated with thyroid cancer incidence.